Bemerkenswerte Alticinenfunde aus Slowenien (Coleoptera: Alticinae) - Doeberl, Manfred (Acta entomologica slovenica (Ljubljana), 2000)
Remarkable records of Alticinae are given, among them 22 first records for Slovenia and four records for species not found for more than 50 years.
Keywords: favna; hrošči; zoologija; zoology